The association between monocyte-to-high-density lipoprotein cholesterol ratio and type 2 diabetes mellitus: a cross-sectional study - Yu, Honghai; Yang, Cunqing; Lv, Jiao; Zhao, Yunyun; Wang, Guoqiang; Wang, Xiuge (Frontiers in Medicine, 2025)
ObjectiveType 2 diabetes mellitus (T2DM) is a prevalent chronic condition often associated with low-grade inflammation. Previous studies have indicated that the monocyte-to-high-density lipoprotein cholesterol ratio (MHR) may serve as a novel inflammatory biomarker with potential predictive value for various metabolic diseases. This study aims to investigate the association between the MHR and the prevalence of T2DM in a general population, using data from the National Health and Nutrition Examination Survey (NHANES).MethodsWe conducted a cross-sectional study analyzing data from five NHANES cycles spanning 2007–2016. We excluded individuals aged under 20 years, those with missing data on monocytes, HDL-C, diabetes status, or other key covariates, and extreme MHR outliers. Statistical analyses were performed using SPSS 26.0, EmpowerStats 4.1, Stata 16, and DecisionLinnc1.0. We employed weighted logistic regression models, subgroup analyses, restricted cubic splines (RCS), and threshold analyses were used to assess the MHR-T2DM association.ResultsA total of 10,066 participants met the inclusion criteria, of whom 1,792 were diagnosed with T2DM. The MHR levels in the T2DM group were significantly higher than those in the non-T2DM group. After adjusting for potential confounders, elevated MHR levels were significantly associated with an increased prevalence of T2DM (p < 0.001, OR = 2.80, 95% CI: 1.823–4.287). Subgroup analyses revealed a significant interaction between MHR and T2DM with respect to gender (P for interaction < 0.05), with a stronger association in women. No significant interactions were observed for age, race, education level, poverty income ratio (PIR), body mass index (BMI), smoking status, physical activity, alcohol consumption, or hypertension (P for interaction > 0.05). RCS analysis indicated a significant nonlinear relationship between MHR and T2DM, with a threshold point for MHR identified at 0.51. Above this threshold, the risk of T2DM increased significantly.ConclusionOur findings suggest that elevated MHR levels, particularly above the threshold of 0.51, are significantly associated with an increased prevalence of T2DM. The gender-specific interaction further highlights that women may be more susceptible to the impact of elevated MHR on T2DM risk. These findings suggest MHR as a potential biomarker for early T2DM screening and highlight gender-specific risk factors.